Severe COVID-19 induces autoantibodies against angiotensin II that correlate with blood pressure dysregulation and disease severity - Briquez, Priscilla S.; Rouhani, Sherin J.; Yu, Jovian; Pyzer, Athalia R.; Trujillo, Jonathan; Dugan, Haley L.; Stamper, Christopher T.; Changrob, Siriruk; Sperling, Anne I.; Wilson, Patrick C.; Gajewski, Thomas F.; Hubbell, Jeffrey A.; et al. (Science advances, 2022)
Patients infected with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can experience life-threatening respiratory distress, blood pressure dysregulation, and thrombosis. This is thought to be associated with an impaired activity of angiotensin-converting enzyme 2 (ACE2), which is the main entry receptor of SARS-CoV-2 and which also tightly regulates blood pressure by converting the vasoconstrictive peptide angiotensin II (AngII) to a vasopressor peptide. Here, we show that a significant proportion of hospitalized patients with COVID-19 developed autoantibodies against AngII, whose presence correlates with lower blood oxygenation, blood pressure dysregulation, and overall higher disease severity. Anti-AngII antibodies can develop upon specific immune reaction to the SARS-CoV-2 proteins Spike or receptor-binding domain (RBD), to which they can cross-bind, suggesting some epitope mimicry between AngII and Spike/RBD. These results provide important insights on how an immune reaction against SARS-CoV-2 can impair blood pressure regulation. Anti-AngII autoantibodies may contribute to dysregulated blood pressure and poor oxygenation in hospitalized patients with COVID.